PERAN PUPUK KANDANG DALAM MENINGKATKAN KESUBURAN TANAH DAN PRODUKTIVITAS TANAMAN - Atman Atman (Jurnal Sains Agro, 2020)
The use of manure is one of the efforts made in order to increase fertility of soil and plant productivity. In Indonesia, the potential for manure is very large, especially from cow manure, namely: 35,944,757 tons, 41,690,458 tons, 43,631,280 tons and 45,272,857 tons respectively in 2013, 2014, 2015, and 2016. Manure, before being applied to agricultural land, it is necessary to do the composting process either naturally or using a starter microbial (activator / decomposer) in the form of local micro-organisms (MOL) or commercially available on the market. Its use is able to speed up the composting period of manure to only 10 days. The more doses of manure applied on agricultural land, the fertility of the soil, especially the physical, chemical, and biological properties of the soil increases. Likewise with plant productivity, which has been seen in the first planting season and residues are still found in the second planting season. The use of manure and biological fertilizer is very prospective to be widely developed. Key words: manure, residual, biofertilizer, soil, plant.